BUILDING VOCABULARY: USING THE THESAURUS AND DICTIONARY EFFECTIVELY - Haqberdiyeva Barchinoy; Ravshan Khujakulov (TADQIQOTLAR, 2026)
A rich and precise vocabulary is essential for effective communication in academic discourse. This article will discuss the roles that the dictionary and thesaurus play in expanding and refining vocabulary. The dictionary acts as the chief determinant of the denotative meaning, giving foundational knowledge through elaborate entries and contextual examples (Nation, 2001), while the thesaurus allows for stylistic nuance and lexical variation. Central to this thesis is Khujakulov’s (2024) argument for using these resources in concert with one another to understand more appropriately the nuances of word choice to navigate complexities of choosing words that best align with both the intended meaning and appropriate connotation of the synonyms considered (Cruse, 2000). The article continues to mention the most common pitfalls in dealing with synonyms, including indiscriminate synonym substitution, and describes a strategy to build a productive and robust vocabulary through continued exposure and active use. Through mastering the effective use of such resources, one finds their way to present involved ideas clearly, confidently, and poignantly.